2013
DOI: 10.1186/1471-2458-13-801
|View full text |Cite
|
Sign up to set email alerts
|

TB tracer teams in South Africa: knowledge, practices and challenges of tracing TB patients to improve adherence

Abstract: BackgroundIn 2008–2009 the South African National Tuberculosis (TB) Program (NTP) implemented a national pilot project, the TB Tracer Project, aiming to decrease default rates and improve patient outcomes. The current study aimed to inform the NTP by describing the knowledge, attitudes, and practices of TB program personnel involved with tracing activities.MethodsA self-administered written questionnaire was sent to TB staff, managers and tracer team leaders to assess basic TB knowledge, attitudes and practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
3
4
1
3
Order By: Relevance
“…Lack of regular monitoring and supervision has given to health centers and health posts were found as a barrier to contact tracing of index TB cases in the current study. This study finding agrees with a study conducted in South Africa that showed a lack of adequate supervision and direction from the district or provincial TB managers [20]. The World Health Organization also recommends conducting routine monitoring using standardized methods based on data with documented quality [5].…”
Section: Discussionsupporting
confidence: 87%
“…Lack of regular monitoring and supervision has given to health centers and health posts were found as a barrier to contact tracing of index TB cases in the current study. This study finding agrees with a study conducted in South Africa that showed a lack of adequate supervision and direction from the district or provincial TB managers [20]. The World Health Organization also recommends conducting routine monitoring using standardized methods based on data with documented quality [5].…”
Section: Discussionsupporting
confidence: 87%
“…The fact that some community health workers report having no masks to protect themselves from TB is therefore very concerning. Similar concerns were raised in a study [17] in which 39.1% (n = 270) of community health workers complained about inadequate protection from contracting TB. These fears are not unfounded: In a South African decade-long cohort study, health workers were reported to have a TB incidence of 1,496�32 per 100,000 compared to an incidence rate of 719�37 per 100,000 in the general population [18].…”
Section: Plos Onesupporting
confidence: 53%
“…Although studies report a high risk of TB infection and disease among health care workers in South Africa [17], outreach teams have insufficient training on TB infection prevention and control measures, limited resources for the maintenance of hygiene and short supply of personal protective equipment [18]. Essential training for outreach teams could include a standardised program with specific emphasis on TB household contact tracing, physical safety when conducting tracing activities such as being provided with personal protective equipment [19] current updates in the field of TB [9,[20][21][22] and field-based training on TB household contact tracing [23]. An approach that includes directed, structured training on contact tracing activities would also be beneficial to the ongoing COVID-19 response.…”
Section: Plos Onementioning
confidence: 99%